Experimental comparison and CFD analysis of conventional shell and tube heat exchanger with new design geometry at different baffle intervals - İNAN, AHMET TALAT (My University, 2022)
Basically, in the working principle, the transition from high temperature to low temperature is achieved, while the temperature value of the one with the lower temperature rises, this process can continue until the temperature value of the other decreases and reaches equilibrium. Therefore, heat exchangers are highly preferred in the industry where heat transfer is possible, in mass production facilities where nonstop production takes place such as the pharmaceutical and paper industry, and in sectors where energy efficiency is of utmost importance. In the analyses, it is aimed to investigate the changes in the fluid behavior of the conventional one-piece type baffle plate shell and tube heat exchanger at different baffle plate intervals by keeping it constant at different flow rates. Here, water was used as the working fluid to examine the changes in fluid behavior, the direction in which the heat transfer rate per pressure drop changes, the pressure drop and the effects on the body side heat transfer coefficient. As a result, it has been determined that the distance between the baffle plates used in the conventional one-piece type shell and tube heat exchanger varies and the values compared at different flow ranges differ.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; TERMODİNAMİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MEKANİK; THERMODYNAMICS; ENGINEERING; Engineering, Computing & Technology (ENG); MECHANICS; Genel Mühendislik; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Physical Sciences